Implementation of the Virtual Learning Models during the Covid-19 Pandemic: Students’ Perspectives and Its Lessons - Naim, Sidrotun; Mokodenseho, Sabil (Jurnal Kependidikan, 2022)
This study aims at analyzing the existence of the implementation of the virtual learning models during the Covid-19 pandemic to encourage, explore, and evaluate effective online learning based on the students’ perspectives. This type of research is library research using qualitative descriptive methods. Data in this study were students’ perspectives from many contemporary literature sources, such as journals, books, and other relevant works of literature. By using the Connectivism theory and the PICRAT model, the results indicated that students faced many problems during the Covid-19 pandemic due to inexperienced teachers. Furthermore, the online system was not equipped with optimal learning infrastructure, giving rise to negative and positive aspects in many aspects of learning. Both teachers and students in countries affected by the Covid-19 pandemic faced similar problems, namely the online learning system which was not handled properly. Thus, with a proper understanding of the strengths and limitations of online learning, it is feasible to offer a better instructional atmosphere for students by making appropriate modifications. This study concludes that online learning and the dynamics of education reform still serve as a model for future educational development, especially for facing a pandemic. The significant contribution of this study is the findings regarding the potential of technology and the barriers that students face while learning due to digital mechanisms.